Scheduling links with air-time in multi transmit/receive wireless mesh networks - Xu, Y.; Chin, K.; Soh, Sie Teng; Raad, R. (Springer, 2016)
A key advance in enabling higher wireless mesh network capacity is allowing routers to transmit or receive (MTR) from multiple neighbors simultaneously over the same frequency. Achieving this capacity, however, is predicated on a link scheduler that is able to capitalize on the MTR capability of nodes to activate the maximum number of active links, and also to derive the shortest schedule that ensures all links are activated at least once. To date, existing schedulers do not consider the transmission or air-time of packet(s). Henceforth, this paper fills this gap and propose to derive the shortest superframe length, defined as the end time of the last transmitting link. Our scheduler, called A-TxRx, greedily adds links whenever a link finishes its transmission. As a result, unlike previous schedulers, links can start transmitting/receiving as soon as there is no conflict. We have evaluated the performance of A-TxRx in various network configurations, and compared it against two state-of-the-art approaches: 2P and JazzyMAC. The results show A-TxRx outperforming these algorithms significantly, especially when the network becomes denser. Specifically, the superframe length of A-TxRx is typically less than half of 2P and JazzyMAC, with 60 % more concurrently transmitting links.